2003
DOI: 10.1074/jbc.m305469200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elements Contribute to the Calcium/Calmodulin Dependence on Enzyme Activation in Human Endothelial Nitric-oxide Synthase

Abstract: Two regions, located at residues 594 -606/614 -645 and residues 1165-1178, are present in the reductase domain of human endothelial nitric-oxide synthase (eNOS) but absent in its counterpart, inducible nitric-oxide synthase (iNOS). We previously demonstrated that removing residues 594 -606/614 -645 resulted in an enzyme (⌬45) containing an intrinsic calmodulin (CaM) purified from an Sf9/baculovirus expression system (Chen, P.-F., and Wu, K.K. (2000) J. Biol. Chem. 275, 13155-13163). Here we have further elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…This indicates that phosphorylation of eNOS increases the association between eNOS and caveolin. As such, our in vitro data are consistent with the hypothesis that Thr-495 phosphorylation negatively regulates eNOS activity (13,20,22,44,52,55,56). Previous reports have indicated that phosphorylation of eNOS at Ser-1177 leads to a dissociation of eNOS and caveolin; however, this dissociation was dependent upon the induction of caveolin-dependent endocytosis (57,58).…”
Section: Discussionsupporting
confidence: 81%
“…This indicates that phosphorylation of eNOS increases the association between eNOS and caveolin. As such, our in vitro data are consistent with the hypothesis that Thr-495 phosphorylation negatively regulates eNOS activity (13,20,22,44,52,55,56). Previous reports have indicated that phosphorylation of eNOS at Ser-1177 leads to a dissociation of eNOS and caveolin; however, this dissociation was dependent upon the induction of caveolin-dependent endocytosis (57,58).…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with the autoinhibitory insert and C-terminal regulatory elements being required to block heme reduction in CaM-free NOS (26,35,40). Regarding heme reduction in the CaM-bound mutants, Glu 762 is clearly the most important of the six acidic residues because Arg and Ala substitutions at this position slowed down nNOS heme reduction by 95% and caused corresponding decreases in NO synthesis activity.…”
supporting
confidence: 60%
“…The structural comparisons shown in the present report also confirm that these residues have the potential to confer additional functional control on the NOS isoforms. This was demonstrated amply by the work of Roman and colleagues (24,25) prior to any structural information and was confirmed and extended by other laboratories (29,43).…”
Section: Expression and Purification Of Cypor And Cypor Plus C Terminmentioning
confidence: 63%
“…Also, the ability, particularly in eNOS, to control the production of NO through phosphorylation of Ser-1197 in the C-terminal tail (26,27,42) is extremely important for function. Recent reports have addressed the consequences of the truncation of the C-terminal sequences of NOS on the various activities of the enzyme (24,25,29,43).…”
mentioning
confidence: 99%